2021
DOI: 10.1111/jfpp.15328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying on physicochemical and functional properties of stingless bee honey

Abstract: The study aimed to evaluate the effect of drying on the functional quality of stingless bee (Heterotrigona itama) honey. The honey was subjected to vacuum drying (40–60°C), vacuum evaporation (40–60°C), and freeze drying, respectively, to achieve a standardized moisture content. The dehydrated honey seemed to have a significant (p < .05) darker color (lower L* and higher b* values) as compared to the raw honey. Results suggested that the dryness of the dehydrated honey has significantly affected its antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…Although there are studies involving improvements in honey processing, such as spray drying process (Cuevas-Glory, et al, 2017), thermal dehydration (Chen et al, 2021), pasteurization (Schvezov et al, 2020), moisture reduction by alternative technique in unglazed clay pots with different areas of surface diffusion (Mohamad Ghazali et al, 2021), thermosonication (Chong et al, 2017), among others, we do not advocate the use of processing techniques, thus maintaining the true honey identity, with its own contents and sensory characteristics, without processing to increase its shelf life. Indeed, a study carried out by Braghini and collaborators showed that honey storage from stingless bees at 4° for 365 days maintained its stability, with preservation of bioactive characteristics and physicochemical properties (Braghini et al, 2020) and that stingless bees honey, when stored in good conditions, maintains its stability for up to three years (Jimenez et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Although there are studies involving improvements in honey processing, such as spray drying process (Cuevas-Glory, et al, 2017), thermal dehydration (Chen et al, 2021), pasteurization (Schvezov et al, 2020), moisture reduction by alternative technique in unglazed clay pots with different areas of surface diffusion (Mohamad Ghazali et al, 2021), thermosonication (Chong et al, 2017), among others, we do not advocate the use of processing techniques, thus maintaining the true honey identity, with its own contents and sensory characteristics, without processing to increase its shelf life. Indeed, a study carried out by Braghini and collaborators showed that honey storage from stingless bees at 4° for 365 days maintained its stability, with preservation of bioactive characteristics and physicochemical properties (Braghini et al, 2020) and that stingless bees honey, when stored in good conditions, maintains its stability for up to three years (Jimenez et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Table 1 demonstrates that the 5-HMF content was significantly higher for the D, S, H, P, and M treatments compared to the fresh and R samples. Lower water activity can facilitate the Maillard reaction and thus increases the HMF content (Chen et al, 2021). Also, honey can crystallize during storage.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…A study showed that the moisture content of the SLBH was reduced from 31.9 to 11 and 5% after the dehydration process using vacuum and freeze-drying methods [ 21 ]. As presented in Table 1 , the vacuum drying and freeze-drying at 5% moisture setting could achieve an 84.3% reduction in water content.…”
Section: Physicochemical Properties Of Dehydrated Stingless Bee Honeymentioning
confidence: 99%
“…A study by Chen et al [ 21 ] showed that dehydration processes using vacuum and freeze-drying methods at a 5% moisture setting were able to reduce the water activity level from 0.79 to less than 0.3, as presented in Table 2 . Meanwhile, the water activity level of the vacuum drying and evaporation at an 11% moisture setting could reduce the water activity level to less than 0.5.…”
Section: Physicochemical Properties Of Dehydrated Stingless Bee Honeymentioning
confidence: 99%
See 1 more Smart Citation